Fiscal Sustainability and Macroeconomic Determinants of Public Debt: Insights from Morocco 2000–2023 - Wiame , EL HAJJAMI; zahira , EL IDRISSI; HASSANI , Hafid EL; Abdelmouneim , MAJD; Salma, BAKKALI; Ayoub, QASSID (Journal of Ecohumanism, 2025)
This paper investigates the dynamic relationship between some main macroeconomic variables, namely, inflation, interest rate, exchange rate, the GDP growth and budget deficit, and the public debt in Morocco between 2000 and 2023. Using a Restricted Error Correction Model (RECM), the study shows that the budget deficit is the primary engine of debt accumulation. We show that inflation and interest rates have different effects in the short and the long run; GDP growth is hiring for public debt in the short run but in the long run reduces it, emphasizing that macroeconomic stability and sustained growth is key. This research sheds light on the impact of global financial crises and the COVID-19 pandemic on the debt dynamics within Morocco, an underreported but unique economic context. By offering novel insights into the dynamics of macroeconomic fundamentals and public debt, the findings provide a strong basis for future academic studies while suggesting implications for enhancing fiscal discipline and long-term debt sustainability.